Developmental and molecular characterization of novel staminodes in Aquilegia. (18th February 2020) - Meaders, Clara; Min, Ya; Freedberg, Katherine J; Kramer, Elena
Abstract: Background and Aims: The ranunculid model system Aquilegia is notable for the presence of a fifth type of floral organ, the staminode, which appears to be the result of sterilization and modification of the two innermost whorls of stamens. Previous studies have found that the genetic basis for the identity of this new organ is the result of sub- and neofunctionalization of floral organ identity gene paralogues; however, we do not know the extent of developmental and molecular divergence between stamens and staminodes. Methods: We used histological techniques to describe the development of the Aquilegia coerulea 'Origami' staminode relative to the stamen filament. These results have been compared with four other Aquilegia species and the closely related genera Urophysa and Semiaquilegia . As a complement, RNA sequencing has been conducted at two developmental stages to investigate the molecular divergence of the stamen filaments and staminodes in A. coerulea 'Origami'. Key Results: Our developmental study has revealed novel features of staminode development, most notably a physical interaction along the lateral margin of adjacent organs that appears to mediate their adhesion. In addition, patterns of abaxial/adaxial differentiation are observed in staminodes but not stamen filaments, including asymmetric lignification of the adaxial epidermis in the staminodes. The comparative transcriptomics are consistent with the observed lignification of staminodes and indicate that stamen filaments are radialized due to overexpression of adaxial identity, while the staminodes are expanded due to the balanced presence of abaxial identity. Conclusions: These findings suggest a model in which the novel staminode identity programme interacts with the abaxial/adaxial identity pathways to produce two whorls of laterally expanded organs that are highly differentiated along their abaxial/adaxial axis. While the ecological function of Aquilegia staminodes remains to be determined, these data are consistent with a role in protecting the early carpels from herbivory and/or pathogens.